P3.385 Comparative Experience and Outcomes of Clinic Staff Versus Intensive Researcher Led Recruitment to a Sexual Health Intervention in UK Primary Care. (13th July 2013) - Cassell, J A; Dodds, J; Lanza, S; Low, N; Roberts, T; Smith, H E; Rait, G
Abstract : Background: As part of a national randomised controlled trial, we attempted to recruit young people for Chlamydia testing and partner notification interventions in UK general practises (primary care clinics). Practices were paid for recruitment which was managed by clinic staff. Despite training, there were barriers to testing and recruitment: staff experienced competing priorities, were reluctant to mention testing, perceived that STIs were uncommon in their population, and believed that few young people attended the clinic. We aimed to assess the effect of intensive researcher led recruitment on testing rates and compare with prior optimised recruitment by clinic staff. Methods: Ten general practises in North and South East England agreed to participate. We trained research staff on recruitment processes and allocated a researcher to each general practise. The researcher approached potentially eligible young people in the waiting room for a three week period and offered Chlamydia testing and trial enrolment. We compared testing and recruitment rates with those achieved by clinic staff over a period of 3 months. Results: 1145 16–25 year olds were approached in the 10 practises during intensive recruitment periods, of whom 43% consented and tested. Of refusals, 37% had tested elsewhere. Most practises achieved 45–50 tests per 3 week period, compared with 3–4 per month during 3 months of optimised clinic staff recruitment. Conclusion: External researcher led intensive recruitment increased testing levels substantially and should be considered as an alternative to clinic staff enrolment in primary care. Even if enrolment targets are met, the impact of sexual health interventions in primary care will be limited unless barriers to engagement in sexual health are overcome.